Should I wait or should I go? Travelling versus waiting for better healthcare - Matteo Lippi Bruni; Cristina Ugolini; Rossella Verzulli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2021)
We study patient mobility in the Italian National Health System, using patient-episode level data on elective Percutaneous Transluminal Coronary Angioplasty procedures over the years 2008-2011. We examine how patients' choice of the hospital is affected by changes in waiting times and clinical quality within hospitals over time. We estimate mixed-logit specifications and show the importance of jointly controlling for timeinvariant and time varying clinical quality to identify the effect of waiting times. Conversely, failure to capture variations in clinical quality over time does not affect the estimate of the discouraging effect of travel distance. We provide evidence that patients are responsive to changes in waiting times and clinical quality: average demand elasticity with respect to own waiting times and mortality is estimated to be - 0.17 and - 1.38, respectively. Patients' personal characteristics significantly influence how they trade off distance and waiting times with quality of care. We find a higher WillignessTo-Wait and Willingness-to-Travel to seek higher quality care for patients in the younger age groups and who are more severely ill. The results convey important policy implications for highly regulated healthcare markets.
Keywords: I11; I18; R22; 330; patients' mobility; hospital choice; travel distance; waiting times; healthcare quality; mixed logit models